Tradição e tabu: um estudo sobre gênero e sexualidade nas religiões afro-brasileiras - Santos, Milton Silva dos (2007)
This study aims to investigate the presence of homosexuals (sometimes predominant) inside Afro-Brazilian religions. More specifically this dissertation analyzes the relationship between male homosexuality and candomblé . This fact has been studied by many anthropologists for decades. Ruth Landes, Peter Fry, Patrícia Birman, Maria Lina Leão Teixeira, Luís Felipe Rios are among those who have investigated this theme under many different perspectives. When compared to other religions, it is clear that afro-Brazilian religions are more tolerant towards homosexuals. They are allowed to occupy all the available posts in the sacerdotal hierarchy. This is possible because the negatives aspects stigmatized and marginalized sexual identities become partly reduced in the religious spaces. candomblé is a religion that has little sexual preferences discrimination. But even inside this afro-Brazilian religion homosexuality is a delicate subject rarely discussed in the worship places. By conducting field work among candomblé priests and examining the literature it became clear that gender and sexuality also regulates the relationships among the faithful. Therefore, sexuality is still a taboo within Afro- Religious communities